Thermal switch material for modulation of conducted heat in smart windows - Haw, Chee Yeng (Nanyang Technological University, 2021)
Growth & advancement in smart window technologies have brought by tremendous energy efficiency capabilities to homes & buildings by reducing the needs of Heating, Ventilation & Air-Conditioning (HAVC) systems. This reduces the impact on the environment caused by burning of fossil fuels to meet these energy needs for these systems. There are still untapped potentials in researching modulation of conducted heat as most smart window modulates radiated heat. Predecessors of this research concluded that glaze made from graphene quantum dot (GQD) thin films coated on ITO glass & switching component using graphene decorated nanoparticles are ideal materials in constructing a heat modulating smart window. This project focuses solely on improving the switching component material, by synthesising a few series of Magnetic Nanoparticles (MNPs) with different Poly-vinylpyrrolidone (PVP) & graphene concentration variations. Synthesis method used was a modified co-precipitation method & testing for an optimized parameter to achieve optimal thermal performance in modulation conducted heat was conducted. Results & analysis shows that cobalt ferrite MNP samples B0C5 & B0C15 were recommend for this switch application. Some findings include the need for calcination of samples to remove excess PVP & sodium chloride contaminants to enhance the purity & size of the particles. Magnetic properties were not justified due to lack of testing & finalized heat modulating switch was not fabricated. For the continuation of this project, resynthesized of recommended samples & validation testing is important and incorporation of the switch with heat conductive glaze & heatsink into a single prototype is recommended.